Polypoidal Choroidal Vasculopathy - Mirza Metita; Yorihisa Kitagawa; Hiroyuki Shimada; Hiroyuki Nakashizuka (IJRETINA (International Journal of Retina), 2018)
Introduction: to report a case of PCV that has been successfully treated with intravitreal injection of  t-PA,  ranibizumab, and pneumatic displacement.